THE UTILIZATION OF ARTIFICIAL INTELLIGENCE COMPONENTS IN TECHNOLOGY ERA’S LEARNING - Lili Halimah; Arnie Fajar; Yayuk Hidayah; Anis Suryaningsih (Program Studi PGSD Universitas Flores, 2021)
This study was to analyze the importance of component utilization of Artificial Intelligence (AI) in learning. This study was acknowledged by the results of a survey to the secondary school education teachers in the Subject Teachers' Association (MGMP) for Citizenship Education field in Cimahi as many as 42 schools and 146 teachers through the Google Form application and 104 teachers responded according to the Krejcie and Morgan tables. The method used in this research was descriptive survey. Based on the survey results, the main findings in this survey were not very encouraging, because most teachers in the learning process were not always even inclined. They sometimes never used technological media, social networks, use current issues, and assigned learning material widely and in depth. Further research on teachers must be able to master technological assiatance in to make the Citizenship Education was more crucial and urgent for students. On the other hand, students must be able to utilize social media in the daily lives. The school should also provide internet access for the continuation of the learning process. Thus, the government must be able to provide internet access for schools in remote areas, so that technology-based learning is no longer a barrier for teachers and students